S73 Macrophages as vehicles for delivering cell therapy to injured lung. (2nd December 2011) - McNulty, K; Scotton, C J; Sage, E K; Chambers, R C; Janes, S M
Abstract : Introduction: Injury to the alveolar epithelium underlies a number of important lung diseases, exemplified by the syndromes of acute lung injury and acute respiratory distress syndrome, which currently have a poor prognosis. Keratinocyte growth factor (KGF) is a mitogen for, and exerts beneficial effects on, type II alveolar epithelial cells. Pre-treatment with KGF is associated with improvements in outcomes in animal models of lung injury, but the use of recombinant KGF as a clinical therapy is limited by its short bioavailability and lack of specificity. We sought to determine whether macrophages could be used as vehicles to deliver KGF therapy to the injured lung. Methods: Macrophages from a murine macrophage cell line (IC-21) were transduced with a lentiviral vector expressing KGF and the reporter gene GFP. Mice were given oropharyngeal (OP) bleomycin to induce lung injury. On days one and three after induction of lung injury, mice were given 3×10 6 KGF-transduced IC-21 cells (or controls) by OP instillation. Mice were sacrificed on day 5, and bronchoalveolar lavage fluid (BALF) was harvested and lungs were processed for histology. For in vivo tracking experiments, IC-21 macrophages were transduced with a lentiviral vector expressing luciferase and mice were imaged longitudinally using real-time bioluminescence imaging. Results: KGF-expression was confirmed in KGF-lentivirus-transduced macrophages, however delivery of these cells was not associated with improvements in measures of alveolar-capillary membrane permeability (BALF albumin) or inflammation (total and differential cell counts) after lung injury. Cells expressing GFP were recovered in BALF, and immunohistochemistry showed groups of cells close to conducting airways. Longitudinal imaging of mice after OP delivery of luciferase-transduced IC-21 cells suggested that cells initially localised to the lungs, but did not persist at 48 h after delivery. Conclusions: KGF-expressing macrophages can be generated using lentiviral vectors, but therapeutic delivery of these cells to the lungs did not improve measured outcomes in the mouse bleomycin lung injury model. Longitudinal imaging suggested that the lack of therapeutic efficacy of KGF-transduced macrophages may be due to their limited survival, and future work should focus on optimising macrophage delivery and survival in vivo.